Treatment of ovarian cancer in advanced stages (One Health & Risk Management, 2021)
Introduction. The ovarian cancer is the most frequent malign neoplasm of the female reproductive system in the countries of Western hemisphere of the planet. About 205.000 cases of this disease are diagnosed worldwide each year. Ovarian tumors (benign and malignant) can occur at any age, but more often occur at 40-50 years. In terms of frequency, they rank second among female genital tumors, with a significant prevalence of benign forms (75-80%). Ovarian cancer is a malignant tumor of epithelial origin (80-90%), which can occur either in an ovary or simultaneously in both ovaries. The risk of ovarian malignancy is higher for patients with breast cancer. As with breast cancer, the genetic factor plays a role in ovarian cancer, but is less pronounced. Ovarian cancer is rare in two or more close relatives of the patient. But if such a situation occurs, then for a woman there is a high risk of developing the disease. The relevance of the problem is that over the last decade it has been characterized by the rapid development of diagnostic technologies and the development of treatment programs for ovarian cancer. Ultrasound, computed tomography, magnetic resonance imaging and Positron emission tomography, various isotope research methods, tumor marker determination, and molecular diagnosis.Purpose of paper: to assess the combined and complex methods of treatment in patients with ovarian cancer found in advanced stages.The practical significance. Based on clinical data, the results of the surgical treatment and the combined (surgical and chemotherapeutic) treatment methods were evaluated, by providing indications and contra-indications on the treatment of ovarian cancer in late stages. The data established from the study performed can be used to guide clinicians in choosing the best choice of conduct and therapy to reduce the morbidity and developmental potential of ovarian tumors. The radiotherapy is indicated when surgical and chemotherapeutic treatment do not deliver the expected results, while the primary and secondary resistance to polychemotherapy does not stop the development of relapses and metastasis in the small basin. Material and methods. This prospective study included 65 patients diagnosed with advanced ovarian cancer, who were treated at the Gynecology and Radiogynecology Department within the Public Medical Sanitary Institution of Oncology from the Republic of Moldova.Results. The patients were aged between 20-80, the mean age being of 55+2; 32% of patients came from rural environment and 68% – from urban environment. The patients were diagnosed with different histological types of cancer, the most frequent form was the serous papillary cystadenocarcinoma – 32%, and a weekly differentiated solid carcinoma was diagnosed in 29% of patients. The patients were treated surgically and via chemotherapy. 100% patients underwent radical treatment (sub- or total hysterectomy, uni- or bilateral anexectomy, with or without the resection of omentum). The most used schemes of poliochemotherapy were CAP and CC.  55% of patients administered Cyclophosphamidum+Doxorubicinum+Cisplatinum, and 20% were treated via TC, CI, CD schemes.Conclusions. The non-addressing to physician and ignorance of medical opinion makes the diagnosis of tumor processes develop into advanced stages, thus the treatment being a palliative one, depending on the evolution of tumor process and distant metastasis.
Keywords: ovarian cancer; treatment in late stages; combined treatment of ovarian cancer; polychemotherapy treatment.